2003
DOI: 10.1271/bbb.67.2655
|View full text |Cite
|
Sign up to set email alerts
|

Specific Incorporation ofL-Glutamine into Volicitin in the Regurgitant ofSpodoptera litura

Abstract: Volicitin, [N-(17-hydroxylinolenoyl)-L-glutamine], was identified as an elicitor of plant volatiles from a Spodoptera exigua regurgitant. It has been proposed that gut microbes synthesize volicitin from glutamine, a predominant amino acid component in the insect gut. However, we found that glutamine was not a major component in the regurgitant of Spodoptera litura, although L-glutamine was exclusively incorporated into volicitin by S. litura fed on diets enriched with various amino acids. This selectivity of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…The conjugation of glutamine with fatty acids was demonstrated in vitro with S. litura gut tissues, 19) M. sexta gut enzyme, 20) and S. exigua gut microbes. 21) Yoshinaga et al have also reported that glutamine was exclusively incorporated into volicitin-related compounds in vivo 22) and suggested that the hydroxyl group was introduced after the conjugation of glutamine and fatty acids. Spiteller et al have implied that the hydroxylation on the 17th carbon chain might be carried out by the bacterial cytochrome P450 enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The conjugation of glutamine with fatty acids was demonstrated in vitro with S. litura gut tissues, 19) M. sexta gut enzyme, 20) and S. exigua gut microbes. 21) Yoshinaga et al have also reported that glutamine was exclusively incorporated into volicitin-related compounds in vivo 22) and suggested that the hydroxyl group was introduced after the conjugation of glutamine and fatty acids. Spiteller et al have implied that the hydroxylation on the 17th carbon chain might be carried out by the bacterial cytochrome P450 enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…A recent analysis of S. litura regurgitate suggests that caterpillars can influence its FAC composition through the selective incorporation of glutamine independently of its dietary concentration (Yoshinaga et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid components of FACs appear to be restricted to glutamine and glutamic acid. Specific incorporation of glutamine into FACs was reported in Spodoptera litura (20), and a coupling enzyme for the glutamine conjugates has been isolated as a membrane-bound protein in gut tissues of M. sexta larvae (21) and in S. litura midgut tissues (22). Surprisingly, it is still not clear what benefit insects gain from FACs that outweighs the elicitation of strong defensive reactions in plants.…”
mentioning
confidence: 99%